1999
DOI: 10.1046/j.1432-1327.1999.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of turnip yellow mosaic virus empty shells and evidence for conformational changes occurring after release of the viral RNA

Abstract: Turnip yellow mosaic virus (TYMV) is a small isometric plant virus which decapsidates by releasing its RNA through a hole in the capsid, leaving behind an empty shell [R. E. F. Matthews and J. Witz, (1985) Virology 144, 318±327]. Similar empty shells (artificial top component, ATC) can be obtained by submitting the virions to various treatments in vitro. We have used differential scanning calorimetry, analytical sedimentation, and electron microscopy to investigate the thermodenaturation of natural empty shell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Several published studies reported DSC analysis of a number of different viruses showing diagnostically unique thermograms that provide an additional means of their characterization, [28][29][30][31]. Unique thermograms for different viruses could be due to differences in the array of proteins that typically decorate viral coat surfaces [30].…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies reported DSC analysis of a number of different viruses showing diagnostically unique thermograms that provide an additional means of their characterization, [28][29][30][31]. Unique thermograms for different viruses could be due to differences in the array of proteins that typically decorate viral coat surfaces [30].…”
Section: Discussionmentioning
confidence: 99%
“…Similar capsid forms (artificial top components, ATCs) can be made by freeze‐thawing (Böttcher and Crowther, 1996; Kaper and Siberg, 1969) and by exposure to conditions such as elevated pH, temperature or pressure. The resultant empty shells differ somewhat according to their mode of origin, but all are distinct from the NTC empty shells, which have no holes (Michels et al ., 1999). High‐resolution structural studies on ATCs are needed to understand how virions are destabilized during decapsidation.…”
Section: A Virus With a Rich History In Structural Studiesmentioning
confidence: 99%
“…This is composed of native or near native protein capsids that lack RNA (Matthews, 1960). A preparation of particles identical in most respects to this top component can be made by thawing intact virions from liquid nitrogen temperatures (Kaper and Siberg, 1969) or by other means such as pH change (Keeling and Matthews, 1982) and high pressure (Leimkuhler et al, 2001) (for reviews, see references (Givord et al, 1972;Kaper, 1975;Michels et al, 1999)). These other preparations are collectively referred to as artificial top component (ATC).…”
Section: Introductionmentioning
confidence: 99%